The utility of historical records for hazard analysis in an area of marginal cyclone influence - Switzer, Adam D. (2023)
Shark Bay Marine Park is a UNESCO World Heritage Property located in a region of marginal tropical cyclone influence. Sustainable management of this unique environment as the climate changes requires a quantified understanding of its vulnerability to natural hazards. Here, we outline a structured analysis of novel historical archive information that has uncovered reports of an extreme storm surge associated with a Tropical Cyclone in 1921 that generated remarkable overland flow which left fish and sharks stranded up to 9.66 km (6 miles) inland. Weighted information from historical archives is placed in a new framework and provide inputs to modelling of this event which improves the understanding of its magnitude and furnishes records of the impacts of what occurred on that day and notably also in the years following. The suite of plausible tracks that reproduce the historical data contextualise the storm as a marginal Category 4 or 5 storm and its return interval as equivalent or slightly greater than the current local planning level for coastal flooding in the region. The outcome underscores the global importance of examining the probable maximum event for risk management in areas of marginal cyclone influence where vulnerable ecosystems or vital regional infrastructure of key economic importance are located, and the need to factor in TC risk in marine conservation and planning in the Shark Bay World Heritage Property.